Plural Marking and d-Linking in Spanish Interrogatives. (3rd February 2020) - Maldonado, Mora
Abstract: What is the semantic import of number morphology? This question has been traditionally addressed by focusing on singular and plural noun phrases. The present work brings interrogative phrases into the picture. We analyse Spanish bare interrogative 'quién' and its plural counterpart 'quiénes'. Unlike which -questions in both English and Spanish, the behaviour of quién- and quiénes -interrogatives cannot be easily explained by most accounts of semantic number. In contrast, we argue that the distribution of these interrogatives in Spanish can be well accounted for by assuming that the plural 'quiénes' triggers a strong plurality presupposition, and can only be used in d-linking contexts, whereas 'quién' carries no specific requirement, as far as its semantics is concerned. As a result, our proposal shows that current approaches to number marking need to be refined in order to account for cross-linguistic and within-language variation.